Navigating E-Commerce Loyalty: The Role of E-Brand Experience and Mediating Factors in Indonesian Millennial Consumers - Setiawan, Sandy; Susan, Marcellia; Istiharini, Istiharini (Aptisi Transactions On Technopreneurship (ATT), 2024)
The rapid growth of e-commerce has driven advancements in internet technology, attracting consumer attention due to its benefits such as flexibility, broader market reach, lower operational costs, faster transactions, a wider range of products, and overall convenience. E-loyalty is crucial for online businesses because customer retention is directly linked to increased profits, making loyal customers the most valuable asset for any company. Millennials, who are wealthy, educated, and tech-savvy, represent the main group engaging in online shopping. To compete in a crowded market and build lasting customer relationships, marketers are increasingly focusing on enhancing the e-brand experience. This study examines the impact of e-brand experience on e-loyalty, with e-commerce in Indonesia serving as a mediating factor among millennials. An online survey distributed via social media collected 516 responses, with 438 meeting the criteria of having made at least two purchases within the past three months. The findings reveal that e-brand experience significantly influences e-trust, satisfaction, and loyalty among millennial consumers. Millennials trust in an e-commerce brand is strongly shaped by their experiences, which are further reinforced by positive feedback from others. A positive brand experience not only increases brand satisfaction but also fosters a strong desire for repeat purchases. For e-commerce platforms, providing excellent customer service and simple, user-friendly processes are essential for building and maintaining customer trust and loyalty.